2003
DOI: 10.1258/09564620360719831
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social network characteristics and exchanging sex for drugs or money among drug users in Baltimore, MD, USA

Abstract: The current study examined social network and drug use factors associated with buying and selling sex among a sample of opiate and cocaine users in Baltimore, Maryland. A sample of 702 drug users who were sexually active were administered a social network and risk behaviour inventory. Compared to 25% of men, only 1.7% of women reported a history of giving money or drugs to get sex during the past 90 days. Conversely, more women (21.2%) than men (4.7%) sold sex for money or drugs. Those who sold sex were more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 13 publications
5
52
0
1
Order By: Relevance
“…Nonetheless, the importance of this finding is magnified by the extremely high risk for HIV infection and transmission among male sex workers (Estcourt et al 2000;Newman et al 2004). Previous studies have linked sex trading behaviors to crack cocaine use (Joe and Simpson 1995;Latkin et al 2003), which is consistent with current analysis of this study's data showing that those who used crack were more likely to be involved in sex trading (Orellana et al 2007). …”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, the importance of this finding is magnified by the extremely high risk for HIV infection and transmission among male sex workers (Estcourt et al 2000;Newman et al 2004). Previous studies have linked sex trading behaviors to crack cocaine use (Joe and Simpson 1995;Latkin et al 2003), which is consistent with current analysis of this study's data showing that those who used crack were more likely to be involved in sex trading (Orellana et al 2007). …”
Section: Discussionsupporting
confidence: 90%
“…Juarez. Although reports vary widely, international literature suggests that 21-80% of female IDUs report ever trading sex for money or drugs (Spittal et al, 2003, Lowndes et al, 2003, Latkin et al, 2003, Kozlov et al, 2006, Benotsch et al, 2004 and 9%-82% of FSWs have ever injected drugs (McMahon et al, 2006, Ward et al, 1993, Vandenhoek et al, 1989, Deren et al, 1997A. Valdez, personal communication, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Juarez found that female IDUs often used drugs within the context of a sexual relationship with a drug using male partner . International literature suggests that female IDUs tend to have greater overlap in their sexual and drug use networks relative to males (Latkin et al, 2003, Sherman and Latkin, 2001, which can contribute to being "second on the needle" , Harvey et al, 1998. In a study of Hispana female IDUs on the U.S. side of the U.S.-Mexico border, Andrade and Estrada highlight the importance of sociocultural and gender norms to be taken into account when considering their vulnerabilities (Andrade and Estrada, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, peer-based interventions have gained momentum as a complementary strategy for influencing behavior change (Friedman et al, 2004;Knowlton et al, 2001;Latkin et al, 1996, Latkin et al, 2003a. Delivered by the peers of drug users, these interventions have aimed at harnessing the positive influence of peer norms to risk reduction.…”
Section: Levels Of Risk Reduction Interventionsmentioning
confidence: 99%